PERFORMANCE RISK-TAKING AS CATALYSTS IN SHAPING TEACHERS’ DIGITAL LEARNING AGILITY - Nur Dania Mohd Rosli; Mas Nida Md Khambari; Kamilah Abdullah; Su Luan Wong; Noor Syamilah Zakaria; Priscilla Moses; Nur Aira Abdrahim (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2025)
This study explores the role of performance risk-taking in shaping teachers’ digital learning agility, focusing on how teachers adapt and innovate in response to challenges of integrating digital technologies into teaching practices. A qualitative case study approach was employed, involving semi-structured interviews with 45 participants, including primary and secondary school teachers, school administrators, and parents. Data were collected through physical and online interviews and analysed using thematic analysis to identify key patterns and insights related to performance risk-taking. Based on the findings, three key categories emerged, including (1) assessing experiences during risk-taking, (2) venturing into challenging conditions, and (3) learning through risk-taking experiences. The study highlights the importance of performance risk-taking to foster resilience and creativity among the teachers and also the need for supportive environments to empower teachers to embrace challenges while using digital technologies.